Epidemiology and Outcome of Sepsis in Adults and Children in a Rural, Sub-Sahara African Setting. (16th December 2021) - Kwizera, Arthur; Urayeneza, Olivier; Mujyarugamba, Pierre; Baelani, Inipavudu; Meier, Jens; Mer, Mervyn; Musa, Ndidiamaka; Kissoon, Niranjan; Patterson, Andrew J.; Farmer, Joseph C.; Dünser, Martin W.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To identify the epidemiology and outcome of adults and children with and without sepsis in a rural sub-Sahara African setting. DESIGN: A priori planned substudy of a prospective, before-and-after trial. SETTING: Rural, sub-Sahara African hospital. PATIENTS: One-thousand four-hundred twelve patients (adults, n = 491; children, n = 921) who were admitted to hospital because of an acute infection. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Demographic, clinical, laboratory data, danger signs, and the presence of sepsis (defined as a quick Sequential Organ Failure Assessment score count ≥ 2) at admission were extracted. Sepsis was observed in 69 adults (14.1%) and 248 children (26.9%). Sepsis patients differed from subjects without sepsis in several demographic and clinical aspects. Malaria was the most frequent type of infection in adults (66.7%) and children (63.7%) with sepsis, followed by suspected bacterial and parasitic infections other than malaria. Adults with sepsis more frequently developed respiratory failure (8.7% vs 2.1%; p = 0.01), had a higher in-hospital mortality (17.4% vs 8.3%; p < 0.001), were less often discharged home (81.2% vs 92.2%; p = 0.007), and had higher median (interquartile range) costs of care (30, 300 [19, 400–49, 900] vs 42, 500 Rwandan Francs [27, 000–64, 400 Rwandan Francs]; p = 0.004) than adults without sepsis. Children with sepsis were less frequently discharged home than children without sepsis (93.1% vs 96.4%; p = 0.046). Malaria and respiratory tract infections claimed the highest absolute numbers of lives. The duration of symptoms before hospital admission did not differ between survivors and nonsurvivors in adults (72 [24–168] vs 96 hr [72–168 hr]; p = 0.27) or children (48 [24–72] vs 36 [24–108 hr]; p = 0.8). Respiratory failure and coma were the most common causes of in-hospital death. CONCLUSIONS: In addition to suspected bacterial, viral, and fungal infections, malaria and other parasitic infections are common and important causes of sepsis in adults and children admitted to a rural hospital in sub-Sahara Africa. The in-hospital mortality associated with sepsis is substantial, primarily in adults.